Energy homeostasis genes and breast cancer risk: The influence of ancestry, body size, and menopausal status, the breast cancer health disparities study. Issue 6 (December 2015) - Slattery, Martha L.; Lundgreen, Abbie; Hines, Lisa; Wolff, Roger K.; Torres-Mejia, Gabriella; Baumgartner, Kathy N.; John, Esther M.
Highlights: Obesity and breast cancer risk is multifaceted and genes associated with energy homeostasis may modify this relationship. Energy homeostasis genes, including CCK, POMC, NPY, LEPR, GHRL, and ADIPOQ, were associated with breast cancer risk. Associations varied by menopausal status, body size, and level of Indigenous American genetic ancestry. Abstract: Background: Obesity and breast cancer risk is multifaceted and genes associated with energy homeostasis may modify this relationship. Methods: We evaluated 10 genes that have been associated with obesity and energy homeostasis to determine their association with breast cancer risk in Hispanic/Native American (2111 cases, 2597 controls) and non-Hispanic white (1481 cases, 1585 controls) women. Results: Cholecystokinin ( CCK ) rs747455 and proopiomelanocortin ( POMC ) rs6713532 and rs7565877 (for low Indigenous American (IA) ancestry); CCK rs8192472 and neuropeptide Y ( NYP ) rs16141 and rs14129 (intermediate IA ancestry); and leptin receptor ( LEPR ) rs11585329 (high IA ancestry) were strongly associated with multiple indicators of body size. There were no significant associations with breast cancer risk between genes and SNPs overall. However, LEPR was significantly associated with breast cancer risk among women with low IA ancestry ( P ARTP  = 0.024); POMC was significantly associated with breast cancer risk among women with intermediate ( P ARTP  = 0.015) and high ( P ARTP  = 0.012) IA ancestry. The overall pathway was statistically significant for pre-menopausal women with low IA ancestry ( P ARTP  = 0.05), as was cocaine and amphetamine regulated transcript protein ( CARTPT ) ( P ARTP  = 0.014) and ghrelin ( GHRL ) ( P ARTP  = 0.007). P OMC was significantly associated with breast cancer risk among post-menopausal women with higher IA ancestry ( P ARTP  = 0.005). Three SNPs in LEPR (rs6704167, rs17412175, and rs7626141), and adiponectin ( ADIPOQ ); rs822391) showed significant 4-way interactions (GxExMenopausexAncestry) for multiple indicators of body size among pre-menopausal women. Conclusions: Energy homeostasis genes were associated with breast cancer risk; menopausal status, body size, and genetic ancestry influenced this relationship.